PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE BERBANTUAN ALAT PERAGA PAPAN PENCERNAAN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP IPA KELAS V SEKOLAH DASAR - Murdani, Eka; Safira, Aisha; Hendriana, Evinna Cinda; Sumarli, Sumarli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims: 1) To determine differences in students' ability to understand science concepts; 2) To find out how big the influence of the think talk write learning model is with the aid of the digestive board props; 3) To find out students' responses to the think talk write learning model with the help of class V teaching aids at SDN 23 Singkawang. The research method used is a quantitative research approach. The research design used in this research is Quasi Experimental design. The population in this study was all class V students. The research design was cluster sampling, totaling 27 people. Data collection techniques in this research used tests and non-tests. The test instrument is a concept understanding ability test, and the non-test uses a questionnaire. The data analysis technique uses a two-sample t test with a significance level of 5% (0.05) and the Effect Size test using Excel. The results of this research show that; 1) The difference in the ability to understand science concepts of students in the Ha category was accepted at 9.71%; 2) The influence of the Think Talk Write Model assisted by the digestive board is in the medium category with a total of 0.43; 3) There is a positive response from students in the very good category, a percentage of 83.56%. It can be concluded that there is an influence of the Think talk write model assisted by a digestive board on students' ability to understand science concepts.